SIMULATOR PANEL PINTU KARGO PESAWAT BOEING 737 – 900 ER OTOMATIS BERBASIS ZELIO SMART RELAY - Anggoro Eko Setyanto; Nurwijayanti KN (Electrical Engineering, Universitas Mercu Buana, 2017)
In the current era is a lot of public transportation that has been provided by the government and private sectors. People now, more inclined to use the mode of transport that is more secure, convenient, and timely in mobility to his destination. One form of technological developments in the world of aviation is the air cargo door system. However, at the Boeing 737-900 ER still uses the cargo door manually. Cargo door mechanical system simulation created automatically by connecting the rotor pulley to load the door so that it can move. To make the program by arranging the ladder diagram and simulated work with Zelio Soft 2 is then transferred from the PC (personal computer) to the device to be tested. Panel system works by switching the green Input Port I1 then the DC motor will rotate to right drive the load to open the door and if the load door has touched a mechanical sensor switch 1 Input Port I3 then the motor stops and by switching the red Input Port I2, the DC motor will drive the load rotates left to close the door and if the door is already touching the load mechanical sensor switch 2 input Port I3 then the motor stops. When the load exceeds the capacity ampere circuit safety In 4A until it reaches the average - average of 7,25 A. The MCB trip to secure the circuit within the average - average of 6,25 seconds and the Power Supply change the voltage of 220 VAC enter into a 24 VDC output voltage, which is taken Data is based on testing of the average - average 210,8 VAC and 23,05 VDC.Kata Kunci— Cargo; Zelio Smart Relay; MCB; Power Supply; sensor